2022
DOI: 10.3390/su142013295
|View full text |Cite
|
Sign up to set email alerts
|

Impact Assessment of Diverse EV Charging Infrastructures on Overall Service Reliability

Abstract: A higher penetration of EVs may pose several challenges to the power systems, including reliability issues. To analyze the impact of EVs on the reliability of power systems, a detailed EV charging infrastructure is considered in this study. All possible charging locations (home, workplace, public locations, and commercial fast chargers) and different charging levels (level 1, level 2, and DC fast charging) are considered, and seven charging infrastructures are determined first. Then, the reliability impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…However, the transition to EVs as a viable solution for reducing greenhouse gas emissions in the transportation sector presents several challenges for the power sector (Khan et al, 2022;Zhang et al, 2022). For example, at the power system level, accommodating the increased demand necessitates additional power plants to cater to EVs' energy needs and serve as reserves (Heuberger et al, 2020).…”
Section: Introduction 1motivationmentioning
confidence: 99%
“…However, the transition to EVs as a viable solution for reducing greenhouse gas emissions in the transportation sector presents several challenges for the power sector (Khan et al, 2022;Zhang et al, 2022). For example, at the power system level, accommodating the increased demand necessitates additional power plants to cater to EVs' energy needs and serve as reserves (Heuberger et al, 2020).…”
Section: Introduction 1motivationmentioning
confidence: 99%
“…A growing body of research has identified positive and negative unintended consequences of the large-scale transition from gas to battery electric vehicles (BEVs).Beyond decarbonization, BEVs have the potential to positively impact air quality and environmental justice [1][2][3][4][5][6] and to provide quality-of-life improvements through Vehicle-to-grid (V2G) technologies as vehicles can be used to power homes during outages 7,8 . However, there are growing questions about BEV carbon efficiency 9, 10 and mass-production feasibility [11][12][13][14][15] and BEVs also introduce challenges for integration into the grid 16 , create infrastructure vulnerabilities 17 and ties between efficiency and consumer behavior 18 .BEVs also pose a challenge to owners during natural disasters 19,20 . Electric vehicles couple transportation and electric power systems and this link poses a risk of power outages making transportation unavailable during disasters and limiting mobility for BEV owners during power outages.…”
mentioning
confidence: 99%
“…BEVs also pose a challenge to owners during natural disasters 19,20 . Electric vehicles couple transportation and electric power systems and this link poses a risk of power outages making transportation unavailable during disasters and limiting mobility for BEV owners during power outages.…”
mentioning
confidence: 99%
“…Isograph (England, USA), ITEM iQRAS (England, USA), RAM Commander (Israel), and Windchill Quality Solutions (Relex) (USA) are among the leading software products utilized in the realm of reliability analysis. These are integrated software tools that include various methods of analysis, implement various forms of model setting (graphs, failure trees, event trees, reliability flowcharts), contain extensive databases of initial data, have a developed graphical user interface, are exhaustively documented, have both local and network configurations, are interfaced by import-export with databases, text editors, spreadsheets, logistics software, SAPE [30,[49][50][51][52][53][54][55][56].…”
mentioning
confidence: 99%